EFEKTIVITAS PLATFORM ALEF TERHADAP MOTIVASI BELAJAR SISWA KELAS VII SMP TRISULA PERWARI 2 JAKARTA - Solihin, Ahmad; Laila Salsabila, Nida (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
The development of technology in education is very helpful for teachers in teaching. Students find it easier and faster to acquire literacy with many applications such as: power point, youtube, or e-learning based systems, and platforms as learning aids. The application of the alef platform in Islamic Religious Education (PAI) learning can stimulate the learning process even though teachers face several obstacles. They have many limitations in compiling, designing, designing teaching materials and are less proficient in this application so that it can reduce the KKM value, in addition to the lack of social interaction between teachers and students. This study was conducted to determine the effectiveness of the use of interactive learning media based on the alef platform on student learning motivation at SMP Trisula Perwari 2 Jakarta with a quantitative research paradigm and a field research approach. The results of the study stated that there was a positive influence of the alef platform (X) on student learning motivation (Y) as tested by the adjusted r square (R2) simple linear regression model, which was 0.164 (16.4%).